Effects of rational emotive education module on irrational beliefs and stress among fully residential school students in Malaysia - Mahfar, Mastura; Amat Senin, Aslan; Mohd Noah, Sidek; Ahmad, Jamaluddin; Wan Jaafar, Wan Marzuki (Elsevier, 2014)
This study was carried out to identify the effects of Rational Emotive Education (REE) Module on irrational beliefs and stress among fully residential school students. The research design was true experimental which used pre-test and post-test randomized control group. The subjects of this study were 90 Form One students from three fully residential schools in Johor, Malaysia who were selected using group random sampling and were randomly assigned to the big experimental group (EGB), the small experimental group (EGS) and the control group (CG). All groups responded to the same questionnaires which were the Students’ Beliefs Questionnaire (SBQ) and Students’ Stress Questionnaire (SSQ) before and after the treatment. The data was analyzed by paired samples t-test and one-way ANOVA. The results revealed that 1) there were significant differences between pre-test and post-test in EGB and EGS for irrational beliefs and stress except for CG, 2) there were significant differences between post-test of EGB and CG and also EGS and CG for irrational beliefs and stress, 3) there were no significant differences between post-test of EGB and EGS for irrational beliefs and stress. In conclusion, the REE Module based on the Rational Emotive Behaviour Therapy (REBT) approach, whether implemented via small groups or big groups, is useful in helping fully residential school students to lessen their irrational beliefs and stress.